Platelet-to-high-density lipoprotein ratio as a biomarker for asthma risk in adolescents: insights from NHANES 2011–2023 - Liao, Fangju; Lv, Qi; Xu, Yana; Zan, Jieyu; Xie, Yu (Frontiers in Allergy, 2025)
BackgroundAsthma is a common inflammatory disease among adolescents, with systemic inflammation playing a key role in its development. The platelet-to-high-density lipoprotein ratio (PHR) has emerged as a novel indicator of systemic inflammation. However, while individual roles of platelet count and HDL cholesterol in asthma have been studied, the combined impact of PHR on asthma risk—particularly in adolescent populations—remains unclear and underexplored.ObjectiveThis study aimed to evaluate the association between PHR and asthma risk in adolescents using data from the National Health and Nutrition Examination Survey (NHANES) 2011–2023.MethodsA cross-sectional analysis was conducted on 10,046 adolescents aged 8–18 years from NHANES. Asthma status was self-reported, and PHR was calculated as the ratio of platelet count (1,033 /μl) to HDL cholesterol (mg/dl). Logistic regression models were used to assess the association between PHR quartiles and asthma, adjusting for age, sex, race/ethnicity, body mass index (BMI), and poverty-to-income ratio (PIR). Restricted cubic spline (RCS) analysis was applied to examine non-linear relationships, with sensitivity and subgroup analyses conducted to ensure robustness.ResultsAdolescents with asthma had higher PHR levels compared to non-asthmatic peers (p < 0.001). In fully adjusted models, participants in the highest PHR quartile had significantly higher odds of asthma (OR = 1.59, 95% CI: 1.37–1.83, p < 0.001) compared to the lowest quartile. RCS analysis revealed a non-linear relationship, with asthma risk escalating sharply at higher PHR levels. Subgroup analyses confirmed consistent associations across race/ethnicity, BMI, and PIR categories. Sensitivity analyses excluding participants under 12 years of age yielded similar results.ConclusionPHR is significantly associated with asthma risk in adolescents, highlighting its potential as a cost-effective and accessible biomarker for identifying high-risk individuals. These findings underscore the need for further longitudinal and interventional studies to validate PHR’s role in asthma prediction and management.